Exposure to misinformation, risk perception, and confidence towards the government as factors influencing negative attitudes towards COVID-19 vaccination in Malaysia - Mohamad, Emma; Tham, Jen Sern; Mohd Ajis, Siti Zaiton; Hamzah, Mohammad Rezal; Ayub, Suffian Hadi; Tri Sakti, Andi Muhammad; Azlan, Arina Anis (Multidisciplinary Digital Publishing Institute, 2022)
Introduction: This study explored exposure to misinformation, COVID-19 risk perception, and confidence towards the government as predictors of negative attitudes toward the COVID-19 vaccine. Methods: A cross-sectional survey was carried out from 30 June to 30 August 2021 involving 775 respondents. The survey instrument for the questionnaire was an adaptation from various different studies consisting of five main variables: (1) misinformation about vaccination; (2) risk perception toward COVID-19; (3) attitudes toward the vaccination programme; (4) intention to get vaccinated; and (5) public confidence in the government in executing the vaccination programme. Results: The results of this study indicate that higher exposure to misinformation led to higher levels of negative attitudes toward the COVID-19 vaccine. When the perceived risk of COVID-19 infection was high, mistrust of vaccine benefits was low but there were also higher worries about the future effects of the vaccine. Confidence in the government was associated with lower negative attitudes toward the COVID-19 vaccine. Conclusion: The results of this study may help develop an understanding of negative attitudes toward vaccinations in Malaysia and its contributing factors.